نخلة التمر تاريخ وحضارة : دراسة تاريخية - الراوي، مها أسعد عبدالحميد طه Taha, Maha Asaad Abdulhamid (كلية المأمون الجامعة, 2018)
Arabs could have set up their atmosphere in agriculture (especially the palms' plantation) for getting their food and providing their daily necessities. In addition; they made up their food, shelter and medicine accordingly. They were using the palms in their industry and trading and whatever they needed during their evolution reigns. So it was their food, fantasy and medicine. Although the modern science couldn't reach to such a food to use it in medicine and industries which had been discovered by Arabs in the past times, We find That modern industries used hare date as a main basic element; this indicates one of the twentieth century achievements after the industrial and technical evolution which means that Arabs had preceded the others in this aspect. So, they got the authenticity in this field.
استطاع العرب قديما أن يطوعوا بيئتهم في الزراعة وخاصة في زراعة نخيل التمر وذلك في سبيل الحصول على غذائهم وتوفير مستلزماتهم اليومية، بل إنهم جعلوا منها الغذاء والمسكن والدواء، يدخلونها في صناعتهم وتجارتهم وكل ما يحتاجون اليه في حياتهم خلال مراحل تطورهم المختلفة، فهي غذاؤهم وونيسهم ودواؤهم، علما أن العلم الحديث لم يتمكن من الوصول الى العديد من الغذاء والدواء والصناعات التي اكتشفها العرب قديما، وأن ما نجده من الصناعات التي تدخل التمرة عنصرا رئيسيا في عناصرها في الوقت الحاضر هو من انجازات القرن العشرين بعد حدوث التطور التقني في الصناعة والتكنولوجيا، أي ان العرب سبقوا شعوب العالم في هذا المجال، فكان لهم في ذلك الأصالة.
Keywords: النشاط الزراعي -- نخلة التمر -- الزراعة -- الدراسات التاريخية -- الحضارة التاريخية -- النظام البيئي -- علم الزراعة والفلاحة -- مستخلصات الأبحاث